Educators' Perceptions of Tiktok as a Music Instructional Materials - Riyan Hidayatullah; Muhmammd Jazuli; Suharto Suharto; Muh Ibnan Syarif (Universitas Negeri Semarang, 2021)
TikTok's popularity has grown over the last two years, eliciting both excellent and adverse reactions. While it may appear intimidating to enter such a crowded field of lip-syncers, dancers, gymnasts, comedians, and others, there is absolutely room for everyone in this content-rich atmosphere (Brach, 2020). This research explores the perspectives of Indonesian music educators on TikTok, from informal knowledge to active use in music education. Participants are involved in this qualitative research and secondary material from the internet, such as news articles, documents, and the YouTube platform. The questionnaire was completed by 28 educators, including music teachers, instructors, and lecturers. Searches for digital data were also conducted through 13 Indonesian creator accounts with thousands of followers, particularly those involving conceptions and consistency. The study's findings indicate that the usage of TikTok for music learning media has not been determined and that during remote learning due to the COVID-19 crisis, educators continue to rely on the Zoom Meeting and Whatsapp applications. Because it is limited in time, educators have not observed the effectiveness and efficiency of this program. Educators that use TikTok do this solely for entertainment and to learn from their influencers. The explicit objective of using TikTok for music instruction has not yet progressed to the next level, and discussions concerning TPACK are continuing.